Biofuels and renewable chemicals production by catalytic pyrolysis of cellulose: a review - Hassan, N. S. (Springer Nature Switzerland AG, 2020)
The rise of consumption of traditional fossil fuels has caused emissions of greenhouse gas and deterioration of air quality. Biomass is a promising substitute for fossil fuels because biomass provides biofuels and chemicals by thermochemical conversion such as pyrolysis. In particular, fast pyrolysis of biomass cellulose into chemicals and biofuels has recently drawn attention. Issues of commercialization of fast pyrolysis products include low heating value, low stability, and high oxygen content and acidity. Consequently, new catalysts for enhanced cellulose conversion are sought for. Here, we review the production of biofuel and renewable chemicals from cellulose pyrolysis using acidic and basic catalysts. Acidic catalysts are more suitable to produce biofuels containing about 50% aromatic hydrocarbons, compared to basic catalysts which give biofuels containing 15% aromatic hydrocarbons. Basic catalysts are preferred to produce renewables chemicals, particularly ketone compounds. We explain the mechanism of cellulose pyrolysis with acidic and basic catalysts. The strong acid sites on the catalyst facilitate high selectivity for aromatic compounds in the pyrolysis oil, whereas basic active sites induce double-bond migration, increase carbon-coupling reactions, and ketone production.